Gabon : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that Gabon's growth performance has recently been strong, but fiscal pressures have increased significantly. Real GDP growth has averaged about 6 percent in the last four years on the back of substantial scaling-up of capital spending as the authorities implement their strategy Plan Strategique Gabon Emergent to promote economic diversification and growth inclusiveness. The medium-term growth outlook has weakened as a result of the sharp decline in oil prices, but is expected to remain relatively strong. Growth is expected to be driven by a number of projects under way in agro-industry, mining, and wood processing.